(untitled) (Bangladesh Journal of Plant Taxonomy, 2014)
The present article tried to document the ethnomedicinal uses of plants and determine the consensus factor among villagers of Kalenga forest area to evaluate the potential for new drugs of herbal origin. This study was conducted in 2010 using semi-structured questionnaire with villagers engaged in the forest management. The present study documented 35 plant species under 25 families for treatment of 11 categories of ailments using 52 medicinal formularies in Kalenga forest area. There was great agreement among the informants regarding ethnomedicinal uses of plants with Factor of Informants Consensus (FIC) value ranging from 0.50 to 0.95, with an average value of 0.73. The study revealed that most of the informants agreed in the use of Litsea glutinosa (Lour.) Roxb. to treat dysentery (FIC 0.95) that showed the highest fidelity level (95.23%). The results of the study also indicated that L. glutinosa might be used for the development of new, cheap, effective, and eco-friendly herbal formulations for healthcare management. Villagers views and our observations confirmed that L. glutinosa is a rare plant in the study area. Illegal and unsustainable collection of bark from this tree by the local crude drug traders considered as major causes of its depletion from nature. DOI: http://dx.doi.org/10.3329/bjpt.v21i1.19272 Bangladesh J. Plant Taxon. 21(1): 83-91, 2014 (June)